NOx, PM and CO2 Emission Reduction in Fuel Combustion Processes - Kosowska-Golachowska, Monika; Czakiert, Tomasz (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Nowadays, fossil fuels are still the main source of primary energy in power generation, transport, and industry in general. Therefore, issues regarding environmental protection, and in particular, air protection, are of great importance. Hence, they have become a key part of the global policies of most developed countries. This Special Issue of Energies, entitled "NOx, PM, and CO2 Emission Reduction in Fuel Combustion Processes", deals with various methods and reduction technologies targeting pollutant emissions, especially NOx, CO2, and particulate matter, associated with different fuel combustion processes. This topic is focused mainly on conventional hydrocarbon fuels; however, we consider biofuels as well.